2022
DOI: 10.3389/fevo.2022.815996
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Patterns of Three Widespread Carnivores—The Wolf, Snow Leopard, and Red Fox—in the Trans-Himalayan Landscape of India

Abstract: The Trans-Himalayan landscape is an extreme cold desert with limited diversity and a low density of wild prey. The landscape has three widespread carnivores—the wolf Canis lupus chanco, snow leopard Panthera uncia, and red fox Vulpes vulpes—competing for similar prey. We studied predation patterns, dietary competition, and niche segregation of three sympatric carnivores in the Indian Trans-Himalayas. The Himalayan or wooly wolf is one of the oldest lineages and has adapted to extreme cold. We further studied t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 86 publications
3
5
0
Order By: Relevance
“…As canid generalist-opportunist species, the wolf and red fox consumed similar prey, albeit the red fox may have obtained livestock and ungulate species via scavenging or by preying on very young individuals (Hacker et al, 2022). Recent research has found that the red fox may coexist with the wolf by exploiting a broader niche (Shrotriya et al, 2022). This was confirmed by occupancy model in our study, where significant differences in the relationship with NDVI between wolf and red fox were observed.…”
Section: Discussionsupporting
confidence: 86%
“…As canid generalist-opportunist species, the wolf and red fox consumed similar prey, albeit the red fox may have obtained livestock and ungulate species via scavenging or by preying on very young individuals (Hacker et al, 2022). Recent research has found that the red fox may coexist with the wolf by exploiting a broader niche (Shrotriya et al, 2022). This was confirmed by occupancy model in our study, where significant differences in the relationship with NDVI between wolf and red fox were observed.…”
Section: Discussionsupporting
confidence: 86%
“…al., 2012; Sunarto et al, 2015; Bu et al, 2016), as larger predators try to eliminate competition of small predators by predation or killing of individuals (Palomares & Caro 1999; Jose et al, 2000; Hass 2009). Our result agrees with the nding that prey diversity is one of the ways that red fox reduce the pressure of inter-speci c competition, allowing red fox to coexist with sympatric large predators by exploiting a broader trophic niche(Shrotriya et al, 2022).…”
supporting
confidence: 92%
“…As opportunistic, ambush predators, snow leopard are reported to typically prefer steep and rugged terrain (Jackson & Ahlborn 1989), while wolf are cursorial predators highly adapted to chase their prey over long distances (Husseman et al, 2003). It could be hypothesized that difference in hunting strategies and trophic competotion avoidance might lead to different habitat selection, and subsequent spatial separation facilitate co-existence of the two apex predators (Shrotriya et al, 2022).…”
Section: Trophic Competition Between Large Carnivoresmentioning
confidence: 99%
“…Land use changes have resulted in the fragmentation of wildlife habitats around the world, forcing animals to coexist with humans (Inskip & Zimmermann, 2009 ). Spiti Valley, a cold arid trans‐Himalayan landscape characterized by extreme environment and low species diversity (Shrotriya et al, 2022 ), is one such region threatened by development and tourism boom (Peaty, 2009 ). Tourism, coupled with unmanaged garbage and improper disposal of livestock carcasses, not only facilitates the red fox but also allows free‐roaming dogs, an introduced mesopredator, to thrive, possibly more than the native red fox (Ghoshal et al, 2016 ; Hughes & Macdonald, 2013 ).…”
Section: Discussionmentioning
confidence: 99%